Comparative analysis of differentially abundant proteins between high and low intramuscular fat content groups in donkeys - Tan, Xiaofan; He, Yu; Qin, Yanchun; Yan, Zhiwei; Chen, Jing; Zhao, Ruixue; Zhou, Shenglan; Irwin, David M.; Li, Bojiang; Zhang, Shuyi (Frontiers in Veterinary Science, 2022)
Intramuscular fat (IMF) is an important regulator that determines meat quality, and its content is closely related to flavor, tenderness and juiciness. Many studies have used quantitative proteomic analysis to identify proteins associated with meat quality traits in livestock, however, the potential candidate proteins that influence intramuscular fat in donkey muscle are not fully understood. In this study, we performed quantitative proteomic analysis, with TMT labeling, with samples from the longissimus dorsi (LD) muscle of the donkey. A total of 585,555 spectra were identified from the six muscle samples used in this study. In total, 20,583 peptides were detected, including 15,279 unique peptides, and 2540 proteins were identified. We analyzed differentially abundant proteins (DAPs) between LD muscles of donkeys with high (H) and low (L) IMF content. We identified 30 differentially abundant proteins (DAPs) between the H and L IMF content groups, of which 17 were upregulated and 13 downregulated in the H IMF group. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analysis of these DAPs revealed many GO terms (e.g., BMP receptor binding) and pathways (e.g., Wnt signaling pathway and Hippo signaling pathway) involved in lipid metabolism and adipogenesis. Construction of protein-protein interaction networks identified 16 DAPs involved in these networks. Our data provide a basis for future investigations into candidate proteins involved in intramuscular fat deposition and potential new approaches to improve meat quality in the donkey.